Teaching Dante in the History of Christian Theology - Whitfield, Bryan J. (Religions, 2019)
Outside of core curriculum programs or Great Books classes, few undergraduates who are not literature majors read and discuss Dante's Divine Comedy. This paper describes the redesign of a course in the history of Christian theology as a model for integrating the study of Dante into additional contexts within general education. Reading Dante not only as poet but also as theologian can enhance students' learning and their engagement with medieval theology. A focused reading of Paradiso provides a novel and exciting way for a survey course in historical theology to balance general education's needs for both breadth and depth. At the same time, reading Dante also helps students to experience the significant intersections of culture and theology in the medieval period.